Why observing Li is not the instrument to attain Ren: on the relation between Ren and Li in the Analects - Zhang, Jian (2024)
Ren 仁 and li 禮 are important concepts in Confucian philosophy. The relation between ren and li has also been a topic of interest for scholars from ancient times to the present. As David Wong argues, the relation between ren and li may motivate an understanding of social norms and morality that transcends cultural boundaries (Wong 2021, x2.2). Many scholars have made several influential contributions to this topic. Generally, they interpret li as a means of attaining ren, and consider li’s role in moral self-cultivation to be one of the core characteristics of Confucian philosophy. This article attempts to subvert this notion. I try to demonstrate, at least in the Analects, that Confucius does not hold the idea that observing li is instrumental to attaining ren.